Resource sharing among the maritime libraries in Iloilo City - Mogote, Rosemarie E.; Yang, Jackson V.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This descriptive research sought to describe the state of the maritime libraries' resources in Iloilo City and to determine the prospects for resource sharing and library cooperation through networking.
It also sought to find out the existing resources and facilities of these maritime libraries, current users of their collections, the extent to which these maritime libraries are willing to participate in resource sharing and the type of resource sharing activities they are willing to engage in. The respondents include the seven (7) Chief Librarians of the participating maritime libraries. Data were gathered through a questionnaire distributed personally to the respondents. Interviews and analyses of records were also conducted. The data gathered were compiled, tabulated and analyzed by frequency and percentage distribution. Tables were used to present the data gathered.
Results showed that library cooperation and sharing of library resources have been made possible through informal and mutual understanding among the librarians of maritime libraries in Iloilo City. The findings of this study revealed that as perceived by the Chief Librarians, resources of each respondent library are enough to cater to all the information needs of their institutional users only especially in the field of maritime education. Concluding from the data gathered, the respondent maritime libraries should cooperate with each other in order to make their resources available to other libraries and to the clients in the community.
In response to the information needs, six out of the seven respondent librarians are willing to participate in the cooperative activities for the maritime libraries in Iloilo City. These librarians were willing to share manpower, modify their policies, participate in fund raising activities, work with the school authorities and share expenses in order that the operation of resource sharing will be functional. The maritime libraries in Iloilo City resource sharing shall have the following perceived benefits: a) strengthen the library resources, b) improve library services, and c) reduce duplication of the library resources.
Based from the result of the study, a formal agreement should be established more importantly on the following cooperative activities that the respondents are willing to initiate: a) cooperative cataloging and indexing, b) union cataloging, c) acquisition listing, d) cooperative acquisition, and b) current acquisition listing.
Based on the preference of the respondents and analysis of the present status of maritime schools in Iloilo City, the Directed Network including Specialized Center/Focal Point as resource sharing network model is the most appropriate model. The JBLCF Library has been chosen as the focal point for networking. Moreover, based on the study seminars, workshops and a fora are recommended to be conducted to meet the purpose of library resource sharing among the maritime libraries in Iloilo city. As regards the network system, the Maritime Libraries Information Network or MARLIN was identified as an appropriate system for information network for the Maritime Libraries in Iloilo City.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Naval libraries -- Philippines -- Iloilo City; Library cooperation -- Philippines -- Iloilo City